Public conceptions of mental illness: labels, causes, dangerousness, and social distance. - Link, B G (1999)
OBJECTIVES: The authors used nationwide survey data to characterize current public conceptions related to recognition of mental illness and perceived causes, dangerousness, and desired social distance. METHODS: Data were derived from a vignette experiment included in the 1996 General Social Survey. Respondents (n = 1444) were randomly assigned to 1 of 5 vignette conditions. Four vignettes described psychiatric disorders meeting diagnostic criteria, and the fifth depicted a "troubled person" with subclinical problems and worries. RESULTS: Results indicate that the majority of the public identifies schizophrenia (88%) and major depression (69%) as mental illnesses and that most report multicausal explanations combining stressful circumstances with biologic and genetic factors. Results also show, however, that smaller proportions associate alcohol (49%) or drug (44%) abuse with mental illness and that symptoms of mental illness remain strongly connected with public fears about potential violence and with a desire for limited social interaction. CONCLUSIONS: While there is reason for optimism in the public's recognition of mental illness and causal attributions, a strong stereotype of dangerousness and desire for social distance persist. These latter conceptions are likely to negatively affect people with mental illness.